WOUND AND ITS HEALING: A CONCISE PHYSIOLOGICAL REVIEW - Syeda Yamna Zia et al (Baqai Journal of Health Sciences)
Wound healing is a process of the body replacing devitalized and/or missing tissue in order to fill a cavity and repair damaged skin. The process typically occurs in a coordinated manner taking up time depending upon the nature of the wound. During this time wounds are vulnerable to repeated trauma and breakdown and should be protected where possible. Generally, wounds are healed by four phasestermed as vascularization, inflammation, proliferation, and maturation. A number of factors such as age, weight, nutritional status, immune response, dehydration, inadequate blood supply to the wound, chronic disease, radiations, surgery etc. greatly influence the process of wound healing